The efficacy of sinustrabeculectomy in the modern clinical practice - A.V. Antonova; V.P. Nikolaenko; V.V. Brzheskiy; A.Ya. Vuks (РМЖ "Клиническая офтальмология")
A.V. Antonova1,2, V.P. Nikolaenko1,2, V.V. Brzhesky3, A.Ya. Vuks4 1St. Petersburg State University, St. Petersburg, Russian Federation 2City Multidisciplinary Hospital No. 2, St. Petersburg, Russian Federation 3St. Petersburg State Pediatric Medical University, St. Petersburg, Russian Federation 4V.M. Bekhterev National Medical Research Center of Psychiatrics and Neurology, St. Petersburg, Russian Federation Aim: to assess the hypotensive effect of sinustrabeculectomy (STE) carried out within the "cascade" treatment algorithm for glaucoma. Patients and Methods: this open prospective interventional single-center cohort study was performed in 443 consequently included patients who underwent surgery for primary open-angle non-compensated glaucoma (POAG) and then were under follow-up for 6–24 months. The STE outcomes were evaluated using commonly accepted criteria of "complete success" and "qualified success", as well as "qualified failure" and "complete failure". The analysis of postoperative intraocular pressure (IOP) changes over time was performed using statistical methods. Results: the "complete success" of surgical operation achieved in 305 (68.9%) cases was associated with a significant and long-lasting decrease (at least for two years) in IOP values. The "qualified success", assuming that the renewal of medication therapy was an essential condition for maintaining a steady IOP was reported in 118 (26.6%) cases. Thus, the surgical treatment in combination with the postoperative hypotensive therapy helped to normalize IOP for at least two years in 423 (95.5%) patients of the study group. The "complete" STE failure due to the loss of filtration and the onset of indications for repeat surgery was reported in 20 (4.5%) cases. The triple combination treatment of glaucoma does not preclude from initiating further surgical IOP normalization and can be used safely prior to planned STE. A statistically significant IOP decrease from the baseline was achieved in all patients (even in the "complete failure" cases) at all 3 endpoints of the study (at 6, 12 and 24 months). The most pronounced and stable decrease in IOP during a two-year follow-up was associated with the "complete success" STE. Conclusion: a statistically significant IOP decrease from the baseline was achieved in all patients even after the "complete failure" of the surgical treatment at all endpoints of the study. The most pronounced and stable decrease in IOP during a two-year follow-up was associated with the "complete success" STE. The preoperative IOP level did not correlate with the results of STE and cannot be considered as a factor predicting its success or failure. Keywords: glaucoma, sinustrabeculectomy , intraocular pressure, glaucoma surgery, cascade algorithm, complete success, qualified success, complete failure. For citation: Antonova A.V., Nikolaenko V.P., Brzhesky V.V., Vuks A.Ya. The efficacy of sinustrabeculectomy in the modern clinical practice. Russian Journal of Clinical Ophthalmology. 2023;23(1):21–26 (in Russ.). DOI: 10.32364/2311-7729-2023-23-1-21-26.